INTERPRETATION OF SURAH LUQMAN VERSE 18 AND AL IMRAN VERSE 134 AS AN EMOTIONAL GUIDANCE APPROACH TO JUVENILE DELINQUENCY - Sulhan Hady; Irsyadunnas Irsyadunnas (AL-TAZKIAH, 2026)
Juvenile delinquency is a complex and growing problem in the school environment. Behaviors such as aggressiveness, rule-breaking, low empathy, and difficulty managing emotions are often rooted in students' weak self-control and emotional immaturity. This article examines the interpretations of Surah Luqman, verse 18, and Surah Ali Imran, verse 134, as a basis for values in the emotional guidance approach in schools. Using a qualitative approach grounded in the literature, this article analyzes Quranic verses relevant to the development of humility, anger management, social empathy, and prosocial behavior. The results of the analysis indicate that messages about the prohibition of arrogance, encouragement to restrain anger, and encouragement to be patient and humble can be counseling strategies that support the development of adolescents' emotional intelligence and prevent delinquent behavior in schools. This study offers a conceptual framework for emotional guidance services based on verse interpretation. It examines the relationship between religious values and psychological constructs, integrating Quranic verse interpretation with the theory of emotional regulation and character education.